PENGARUH UJI VARIETAS DAN PEMBERIAN BAHAN ORGANIK TERHADAP PERTUMBUHAN BAWANG MERAH - Luta, Devi Andriani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Shallots are one of the horticultural commodities needed by the community. Increasing the demand for shallots makes improvements to cropping patterns even more. This study aims to see the effect of the variety test and the application of organic matter on the growth of shallots. This study used a factorial randomized block design (RAK) where the factors used were varieties and organic materials, namely municipal waste compost. The variety consists of 3 factors, namely: Bima, Super Philip and Medan Samosir. Municipal waste compost consists of 0 kg/plot, 1 kg/plot and 2 kg/plot. Parameters observed were leaf length (cm) and number of tillers. The results showed that the variety had an effect on growth, namely the length of the plant and the number of tillers. The best variety for plant length was Bima Brebes and the number of tillers was Super Philip.